Perspective Planning and Policy for Commercial Energy Part II Perspective Planning for Petroleum Products and Coal, Conservation of Energy, Inter-Fuel Substitution and the Energy Scene Volume IV - Planning Commission (Planning Commission, 1989)
In Part I of the report (Chapters I to VII) we discussed analytically the problems and issues relating to demand for commercial energy and long run availability of basic energy resources of coal and hydrocarbon in India. We also presented there the perspective plan for the sectors of electricity and hydrocarbon (exploration, development and operation of oil/gas fields). These extensive analyses were based on the results of an indepth study of integrated energy modeling.
Planning Commission Government of India
Planning Commission Government of India